A comparative investigation of Bombyx mori silk fibroin hydrogels generated by chemical and enzymatic cross‐linking. (27th April 2017) - Chirila, Traian V.; Suzuki, Shuko; Papolla, Chloé
Abstract: Fibroin, the major proteinaceous component of the silk fiber produced by larvae of the domesticated silk moth ( Bombyx mori ), has been widely investigated as a biomaterial for potential applications in tissue engineering and regenerative medicine. Following sol–gel transition, silk fibroin solutions can generate hydrogels that present certain advantages when employed as biomaterials, especially if they are cross‐linked. The subject of this study was the self‐cross‐linking of silk fibroin through a process induced by the enzyme horseradish peroxidase (HRP) in the presence of hydrogen peroxide, a method only recently proposed and scarcely reported. The hydrogels were prepared either by physical cross‐linking, by cross‐linking with a natural compound (genipin), or by enzymatic cross‐linking. The products were comparatively characterized in regard to their synthesis and background chemical aspects, physical and optical properties, mechanical properties, secondary structure, swelling/deswelling behavior, enzymatic degradation, and compatibility as substrates for cell adhesion and proliferation. The study confirmed the advantages of the HRP‐induced cross‐linking, which included considerably shorter gelation times, enhanced elasticity of the resulting hydrogels, and improved cytocompatibility. Discrepancies between certain results of this investigation and those reported previously were discussed in detail.